Measuring and validating students’ attitudes towards mathematics in a Nordic context - Pedersen, Pernille Ladegaard; Christiansen, Nadia Moller; Waagepetersen, Rasmus; Nielsen, Soren Albeck (Journal of Education and e-Learning Research, 2026)
Measuring students’ attitudes towards mathematics is important because students’ attitudes influence their mathematical progress. In this study, we administered the Motivation and Attitude (MAT) questionnaire to 4,742 fourth-grade students, aged 10–11 years, from 114 Danish primary schools. The questionnaire was based on the Attitudes Towards Mathematics Inventory (ATMI), but in this study, it was adapted to suit a younger age group than what the ATMI has previously been used. In this process, the questionnaire was reduced from 40 to 32 questions. The questionnaire was designed to measure students’ attitudes towards mathematics in a Danish context. The structural validity and internal consistency reliability of the MAT questionnaire were satisfactory based on confirmatory factor analysis (CFA) and Cronbach’s alpha analysis, and the scores indicate that the MAT questionnaire has adequate internal consistency reliability. The CFA supported the use of a four-factor model; each factor was directly associated with a specific subscale. Correlations between the motivation and enjoyment, and between motivation and self-confidence, were high (0.8), indicating a close connection between the subscales. This may be due to the theoretical background of the concepts, and a continued effort to define attitude may help develop the questionnaire further.